(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The purpose of this research is to know the consumer perception towards organic food products in Delhi NCR. Population of this research is every individual who buy and use the organic product in their consumption. This study is based on Delhi National Capital Region area only. We administered a structure questionnaire and distributed among the consumers of organic products. This research is based on 140 completely filled questionnaires responses. This research confirms that large number of individual purchase the fresh fruits and vegetables. This research concludes that consumer decision making is based on hisher own knowledge and research organic product decision making. The majority of customers have opinioned that organic products are prime priced.